Effect of simulated disturbance by geese on soil temperature and active layer thickness over one growing season - Holm, Hildur Søndergaard (UiT Norges arktiske universitet, 2022)
The Arctic is an area predicted to be strongly affected by climate change, and the extent of permafrost is expected to decrease. The insulating capacity of bryophytes is central in permafrost preservation. In High-Arctic Svalbard, disturbance by geese through grubbing may damage and remove parts of the bryophyte layer in moss tundra. The disruption is expected to lead to increased soil temperatures and shift the vegetation from being dominated by bryophytes to graminoids. This study focuses on how simulated grubbing affects soil temperature and active layer thickness (ALT) over one growing season. The data were collected in central Adventdalen, Svalbard, in a landscape dominated by ice-wedge polygons. Each polygon was characterized by a wet bryophyte-covered centre encircled by a transitional middle part and a dry rim dominated by vascular plants. Plots were established in each part of six polygons and goose grubbing applied manually to each plot in three polygons after snowmelt, while three polygons were left as controls. Organic and moss layer thickness, soil moisture, soil temperature and ALT from each plot were sampled over the season. The plots exposed to simulated grubbing were expected to show an increase in soil temperature and deepening of ALT compared to the control plots. The effect was expected to be stronger earlier in the season and mitigated by a deeper organic and bryophyte layer. No significant effect of grubbing was registered on soil temperature nor ALT, but the plots covered by a deeper layer of bryophytes and organic soil had lower soil temperature and ALT than the other plots. Future research should investigate disturbance at a larger scale over multiple years.